Design an Ultra Wideband Low Noise Amplifier at 6 GHz Applications (International Journal of Engineering and Computer Science, 2016)
This paper presents a ultra wideband low noise amplifier for 6GHz Applications. This proposed LNA is the extension of inductively common source amplifier and in this design we used transistor multifingering techniques in order to reduce noise and improves gain. This LNA is simulated by using UMC .18um CMOS mixed signal/RF process in cadence virtuoso. In this design, used current source biasing, with power supply is 1.8v. LNA achieved gain 19dB and noise figure is 1.8dB at operating frequency range, and input & output return losses are -24dB & -15dB respectively, reverse isolation is -36dB and stability is 4, IIP3 is -10dBm, 1-dB compression point -17dBm and total power consumption is 9mw.